Macrocyclic lactones and ectoparasites control in livestock: efficacy, drug resistance and therapeutic challenges - Lifschitz, Adrian Luis; Nava, Santiago; Miró, María Victoria; Canton, Candela; Alvarez, L.; Lanusse, Carlos Edmundo (Elsevier, 2024)
Macrocyclic lactones (MLs) are the cornerstone of parasite control in livestock due to their broad-spectrum activity against endo (nematodes) and ecto (lice, ticks, mites) parasites. These molecules, introduced into the veterinary pharmaceutical market 40 years ago, have substantially improved animal welfare and productivity by offering extended high efficacy, reducing treatment frequency, and displaying a favorable safety profile. However, their widespread and intensive use has led to a significant challenge nowadays: the development of parasite resistance. This review focuses on the critical link between drug pharmacokinetics (variation in concentration profiles and exposure over time) and pharmacodynamics (drug efficacy) and the ability of both avermectin and milbemycin MLs families to control livestock ectoparasites. This review discusses the integrated assessment of drug behavior in the host, its diffusion into target parasites, and the impact of different pharmaceutical formulations on enhancing drug delivery to infection sites. These are considered critical research/development areas to optimize the use of MLs, preventing treatment failures and finally extending the lifespan of these essential pharmaceutical ingredients. Finally, the importance of the rational use of MLs, guided by parasite epidemiology and pharmacological knowledge, is emphasized as a key strategy to preserve the antiparasitic efficacy of these still very useful molecules.